2023
DOI: 10.3389/fpain.2023.1150264
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal physiological sensing for the assessment of acute pain

Raul Fernandez Rojas,
Niraj Hirachan,
Nicholas Brown
et al.

Abstract: Pain assessment is a challenging task encountered by clinicians. In clinical settings, patients’ self-report is considered the gold standard in pain assessment. However, patients who are unable to self-report pain are at a higher risk of undiagnosed pain. In the present study, we explore the use of multiple sensing technologies to monitor physiological changes that can be used as a proxy for objective measurement of acute pain. Electrodermal activity (EDA), photoplethysmography (PPG), and respiration (RESP) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, skin conductance has been shown to discriminate the presence or absence of pain in postoperative patients with promising sensitivity and specificity (Ledowski et al, 2006). Moreover, recent research has shown that ML, electrodermal activity, photoplethysmography, and respiration measures could predict the presence or absence of pain with accuracies up to approximately 94% (Fernandez Rojas et al, 2023), although this finding was not externally validated. In future, the potential clinical utility of a combination of several physiological measurements for pain classification should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, skin conductance has been shown to discriminate the presence or absence of pain in postoperative patients with promising sensitivity and specificity (Ledowski et al, 2006). Moreover, recent research has shown that ML, electrodermal activity, photoplethysmography, and respiration measures could predict the presence or absence of pain with accuracies up to approximately 94% (Fernandez Rojas et al, 2023), although this finding was not externally validated. In future, the potential clinical utility of a combination of several physiological measurements for pain classification should be explored.…”
Section: Discussionmentioning
confidence: 99%